O papel das coordenadoras pedagógicas no desenvolvimento do estágio supervisionado: em questão o acolhimento e o acompanhamento - Jesus, Ana Eliza de (Universidade Federal de São Carlos, 2024)
The internship is an important stage in the initial training of teachers, as it gives them the chance to get in touch with the professional field, fostering knowledge of the school culture and the process of building a professional teaching identity. This research sought to analyze the perspective of the pedagogical coordinators who work in school management and who receive interns, from a perspective that considers their actions and perceptions of the supervised curricular internship of undergraduate courses. The research used a qualitative, exploratory approach, with questionnaires, document analysis and semi-structured interviews as data collection techniques. The research context was Elementary School I in schools in the municipality of São Carlos, in the interior of São Paulo. The materials collected were analyzed based on content analysis (Bardin, 2011) and, from this, the following axes of analysis emerged: the first: “The place of the internship from the perspective of the pedagogical coordinators” in which the internship is perceived by the coordinators as fundamental for teacher training, as well as the actions carried out with the interns. And the second, “Pedagogical coordination: implications and challenges encountered in the teaching internship process”, which points out difficulties in relation to working dialogues between the institutions (SME, university and schools). The results of the research show that the pedagogical coordinators understand their role with the trainees in developing actions to welcome and accompany them, as well as mediating the work of the teacher in the classroom. However, some weaknesses were also identified with regard to the role of the pedagogical coordinators with the trainees, such as the existence of gaps in the development of their work and in the organization of pedagogical work, resulting from busy routines and the absence of training relationships that cause doubts and lack of clarity in the performance of their role in a more active way. Finally, the supervised curricular internship should be highlighted as an opportunity to contribute to the trainee's learning, leading them to exercise skills such as analysis, reflection and academic articulation with the context of the profession. On the other hand, the development of these capacities can only really be built through the effective role and dispositions of all those involved, in a training community, in a real partnership to strengthen links. A link between the training spaces (university-school) is essential for the development of appropriate processes to offer internships in initial training and the development of teaching practice for learning the profession. With these considerations in mind, at the end of the research we present the need to implement actions that bring universities, the SME, schools and the agents involved closer together, overcoming the preponderance of bureaucracy so that a policy can be designed that favors better working conditions and articulation in the development of the teaching profession and the learning of professional practice in undergraduate courses.
The role of pedagogical coordinators in the development of supervised internships: welcoming and monitoring in question
Keywords: Coordenadoras pedagógicas; Estágio curricular supervisionado; Formação de professores; Educação básica; Pedagogical coordinators; Supervised curricular internship; Teacher training; Basic education; CIENCIAS HUMANAS::EDUCACAO